Experiments on matching markets: A survey - Rustamdjan Hakimov; Dorothea Kübler (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
The paper surveys the experimental literature on matching markets. It covers house allocation, school choice, and two-sided matching markets such as college admissions. The main focus of the survey is on truth-telling and strategic manipulations by the agents, on the stability and efficiency of the matching outcome, as well as on the distribution of utility.
Keywords: C92; D47; D83; 330; Experiments; matching markets; survey